Relayout Tata Letak Gudang Barang Dengan Menggunakan Metode Dedicated Storage - Delia Meldra; Husor Mangibul Purba (Universitas Putera Batam, 2018)
The results of this research is to calculate the total reduction in material handling withinthe warehouse current conditions, on the proposals 1 and 2 and counting the proposedreduction in the total distance of material handling. The results obtained in the initialconditions is 1305.1 m, whereas the proposed one condition, namely a decrease of 1137.07 m168.03 m with a percentage of 12.87% decline, and on condition that the proposed 2 933.28m decreased by 371.83 m from the initial conditions with the percentage of 28.50% decline.This result is a total trip takes material handling for storing and sending existing paintwarehouse.